Condições de saúde dos idosos residentes nos entornos sul e norte do Distrito Federal - Rocha, Suiany Dias (2016)
The aging process is accelerating in Brazil and worldwide. It is estimated that by 2050 has to be more than 2 billion people over the age of 60 years in the world. Brazil follows the change this, since 2020 it is expected that the Brazilian population has about 29 million seniors. Given the importance of developing research focusing on this audience, in this study the objective was to describe the health status of elderly residents in the municipalities of the environs South and North Region Integrated Development of the Federal District and Surrounding Areas - RIDE-DF between 2010 and 2012. for the study was used a descriptive epidemiological study, cross the household survey population based in the municipalities belonging to the surrounding south and north. For data collection was performed participant definition by selection with equal likelihood held in three stages, at the end of the stages were included those who had more than 60 years. Analysis using software SPSS 19.0 and Excel 2010. This study was approved by the Ethics Committee on human and animal medical research at the University of Brasilia under the FR 342534. protocol Search by 112 people aged over 60 years. The results show that most of the participants are female, aged between 60 and 74 years, both women and men. 53.1% of women are widows and 72.9% of men are married or living with a partner. As for the work 58.9% reported being retired or receiving pensions. When asked about their health self-assessment results were positive where 41.9% as very good and good. With regard to health conditions, 51.8% of the elderly are hypertensive, 24.1% reported back problems 22.3% high cholesterol, also addressing the morbidities 13.7% of seniors report having been diagnosed with diabetes , however reports do not seek health services for treatment. From the results obtained in this study, it is clear that this increase in life expectancy of the elderly is a challenge for the management of the three spheres of government. Therefore, it is important to implant specific services for the elderly population not only focused on chronic diseases, but also for the development and maintenance of functional capacity of the individual thus enhancing their autonomy, as well as disease prevention and / or complications.